Conclusion [in 2022 Annual trends and outlook report: Agrifood processing strategies for successful food systems transformation in Africa] - Jenane, Chakib; Ulimwengu, John M.; Tadesse, Getaw (AKADEMIYA2063, 2022)
The 2022 Annual Trends and Outlook Report (ATOR) aims to generate evidence to guide the ongoing transformation of African food systems through well-concerted and targeted policy interventions in the agrifood processing sector. In line with this objective, the report brings together several studies that explore available and emerging evidence and knowledge in a wide range of policy areas related to the processing segment of agrifood value chains. Overall, the studies (1) confirm the emerging opportunities for agrifood industrialization in Africa, driven by increased urbanization and middle-income consumers who look for diversified diets and convenient foods; and (2) shed light on key areas where policymakers and partners should design policies and make investments that strengthen the sector and increase its capacity to provide healthy diets for all.